Hubungan Pembelajaran Pendidikan Agama Islam dengan Pembentukan Akhlak Siswa Kelas V SD Negeri Cijahe Curug Bogor - Marnianti Nervinarsya; Oking Setia Priyatna; Hasan Basri Tanjung (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
In learning Islamic religious education, it is not only taught about the obligation of a Muslim to worship, but in Islamic religious education learning is taught by educators about how to have good morals, how to speak well and politely to anyone, how to have good ethics, and in learning religious education. Islam is taught about matters relating to fellow human beings. Therefore, it is very important to create coaching and moral formation, especially at elementary school age, which is at that age the peak of the personality of students who are very vulnerable to things that are not good from the environment. Through learning Islamic religious education is expected to be able to improve and shape the morals of students for the better. The purpose of this study was to determine the learning of Islamic religious education and the moral formation of fifth grade students at SD Negeri Cijahe Curug Bogor and to find out whether there is a relationship between learning Islamic religious education and the moral formation of fifth grade students at SD Negeri Cijahe Curug Bogor. This study uses a quantitative approach with survey techniques. The results of this study are Islamic religious education learning for class V SD Negeri Cijahe Curug Bogor in the good category. This is based on the number of respondents' answers with the answer "a" as much as 58.3%, the answer "b" is worth 28.8%, the answer "c" is worth 10.8%. With the number of answers the percentage of answers "a" is worth 58.3%. answer "d" is worth 47.5%. This means that learning Islamic religious education is very necessary in the formation of students' morals, especially the fifth grade students of SD Negeri Cijahe Curug Bogor. The moral formation of the fifth grade students of SD Negeri Cijahe Curug Bogor is in the good category. This is based on the number of respondents' answers with the answer "a" 57.3%, the answer "b" is worth 27.4%, the answer "c" is worth 13.3%, the answer "d" is worth 18.2%. From this rxy calculation, it is worth 0.743 the correlation index number obtained is not negative, which lies between 0.70 - 0.90. Referring to the guidelines for the product moment correlation table used, it can be stated that there is a significant relationship between the Islamic religious education learning variable (X) and the moral formation variable (Y). Keywords: Islamic Religious Education Learning, Moral Development